2013
DOI: 10.1007/s11276-013-0632-7
|View full text |Cite
|
Sign up to set email alerts
|

A new technique for multi-cell joint channel estimation in time division code division multiple access based on reduced rank singular value decomposition

Abstract: A new technique for multi-cell joint channel estimation (MCJCE) in time division code division multiple access based on singular value decomposition (SVD) reduced rank technique is proposed in this paper. MCJCE is one of the effective solutions to improve the mobile system performance throughout mitigate the inter-cell interference form the neighboring cells. The increasing complexity of multi-cell system model due to the additional processing of the interferer users will be solved by using SVD reduced rank te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Many studies (see, e.g., [24,[27][28][29][30][31][32][33][34][35][36][37][38]) have shown that significant complexity reduction can be achieved by rank reduction techniques. Among these techniques, the eigenvalue decomposition (EVD) and its related singular value decomposition (SVD) techniques have had growing interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies (see, e.g., [24,[27][28][29][30][31][32][33][34][35][36][37][38]) have shown that significant complexity reduction can be achieved by rank reduction techniques. Among these techniques, the eigenvalue decomposition (EVD) and its related singular value decomposition (SVD) techniques have had growing interest.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation results of the proposed scheme for CDMA interference suppression show a performance significantly better than existing schemes and close to the optimal fullrank MMSE. Moreover, Marzook et al have proposed a novel channel estimation technique based on SVD technique for time division code division multiple access (TD-SCDMA) [30]. The results have shown that the proposed technique improves the performance of the TD-SCDMA system with low-rank processing and low computation complexity.…”
Section: Introductionmentioning
confidence: 99%